Precision casting of Ti-15V-3Cr-3Al-3Sn alloy setting - Nan Hai; Liu Changkui; Huang Dong (China Foundry, 2008)
In this research, Ti-15V-3Cr-3Al-3Sn alloy ingots were prepared using ceramic mold and centrifugal casting. The Ti-15V-3Cr-3Al-3Sn setting casting, for aeronautic engine, with 1.5 mm in thickness was manufactured. The alloy melting process, precision casting process, and problems in casting application were discussed. Effects of Hot Isostatic Pressing and heat treatment on the mechanical properties and microstructure of the Ti-15V-3Cr-3Al-3Sn alloy were studied.